Traditional Wayang Research Productivity: A Bibliometric Analysis - Purbasari, Mita; Carollina, Donna (Humaniora: Journal of Indonesia Culture and Society, 2023)
The aim of the research was to review the productivity of Wayang’s research by using the bibliometric method from the Scopus database. Wayang is a form of traditional art recognized by UNESCO as a Masterpiece of the Oral and Intangible Heritage of Humanity since 2003. It was not obtained easily, especially in terms of the world community’s introduction of shadow puppets. Puppet research has exploded since it was recognized by UNESCO. However, global indexed publications still needed to be enhanced. Analysis of Wayang research from internationally indexed journals, such as Scopus, was required to recognize this opportunity; the object could be seen from a different perspective. The dataset used was ‘Traditional Wayang’, based on documents during 2015-2021 from the Arts and Humanities areas. The search has found 36 papers related to ‘Traditional Wayang’ research. The number of Wayang studies in Scopus-indexed papers remains limited, retaining the Wayang perspective as a traditional object. This is shown by the 36 documents examined, among which only two clusters are produced: performance and change. In order for Wayang research to have great potential and be considered from a wide range of perspectives, including technological, social, economic, commercial, and other, there are still other types of Wayang as an object material.